1985
DOI: 10.1084/jem.161.5.1249
|View full text |Cite
|
Sign up to set email alerts
|

Lack of gene rearrangement and mRNA expression of the beta chain of the T cell receptor in spontaneous rat large granular lymphocyte leukemia lines.

Abstract: In the rat (1), mouse (2), and human (3), most, if not all, natural killer (NK) activity has been shown to be associated with a distinct subpopulation of cells termed large granular lymphocytes (LGL). It has been suggested that, since LGL express some T cell-associated antigens (4) and can grow in vitro in cultures supplemented with interleukin 2 (IL-2) (5) that LGL represent a population of lymphocytes within the T cell lineage. At present, however, there is very little definitive information regarding either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…The dysfunctional NK subset expands and the cytotoxic NK subset decreases in patients with chronic HIV-1 infection compared with those without HIV infection [2]. Unlike T and B cells, NK cells do not require gene rearrangements for their receptor maturation [3,4]. The functions of NK cells are regulated by a number of MHC-I-specific inhibitory NK receptors (iNKRs) and natural cytotoxicity receptors (NCR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The dysfunctional NK subset expands and the cytotoxic NK subset decreases in patients with chronic HIV-1 infection compared with those without HIV infection [2]. Unlike T and B cells, NK cells do not require gene rearrangements for their receptor maturation [3,4]. The functions of NK cells are regulated by a number of MHC-I-specific inhibitory NK receptors (iNKRs) and natural cytotoxicity receptors (NCR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that this funct ion-associated molecule on these CTL is a novel structure, distinct from either the alpha/beta or delta/ gamma TCR [41,42] for several reasons. One, the moieculc is present on the majority of endogeneous peripheral blood NK cells, cells previously shown not to express TCR molecules [4,43,44], and is not present on freshly isolated peripheral blood T cells (these results and Ref. 25).…”
Section: Discussionmentioning
confidence: 57%
“…taneously with 3.2.3 and anti-CD3 (expressed on all mature T cells [30]) mAbs revealed that the majority of the infiltrating CD8 + cells were 3.2.3 positive, but CD3 negative, thus confirming their NK cell phenotype (31)(32)(33). Normal rat SCGs (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…tion system and the "antigen" or substance being identified as foreign by NK cells in the ganglia after gnanethidine treatment, remains unknown (3,31,34). Nevertheless, their recognition of targets does not appear to follow the classical rules of induction and memory pertaining to other lymphocyte classes (1)(2)(3).…”
Section: Resultsmentioning
confidence: 99%